1994
DOI: 10.1164/ajrccm.149.4.8143057
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory load characteristics during ventilatory muscle training.

Abstract: The response of skeletal muscle to training is influenced by both the intensity and nature of the training stimulus. In this study we investigated the characteristics of the ventilatory load applied to the ventilatory muscles during several different modes of ventilatory muscle training. Patients with chronic obstructive pulmonary disease (COPD) performed the following breathing maneuvers: (1) Unloaded hyperpnea (UH), (2) resistive breathing through a fixed orifice (0.5 cm diameter) at frequencies of 15 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…However, it requires build up of negative pressure before flow occurs, and hence, is inertive in nature. BELMAN et al [57] showed that similar work loads were obtained during resistive loading and threshold loading. Whether resistive loading or this inertive loading produces different training effects, remains to be studied.…”
Section: Respiratory Muscle Trainingmentioning
confidence: 78%
“…However, it requires build up of negative pressure before flow occurs, and hence, is inertive in nature. BELMAN et al [57] showed that similar work loads were obtained during resistive loading and threshold loading. Whether resistive loading or this inertive loading produces different training effects, remains to be studied.…”
Section: Respiratory Muscle Trainingmentioning
confidence: 78%
“…Threshold loading has the advantage of being independent of inspiratory flow rate [46], but requires a buildup of negative pressure before flow occurs, and hence, is inertive in nature. Belman et al [61] showed that similar workloads were obtained during resistive loading and threshold loading. Threshold loading enhances velocity of inspiratory muscle shortening [62].…”
Section: Respiratory Muscle Trainingmentioning
confidence: 82%
“…BELMAN et al [44] investigated the characteristics of the load applied to the inspiratory muscles using four methods of overload: flow resistive, pressure threshold, maximal isometric contraction (Mueller manoeuvre) and unloaded hyperpnoea. Whilst there were some similarities between the methods in terms of the stimulus delivered to the muscles (e.g.…”
Section: Specificitymentioning
confidence: 99%